2010
DOI: 10.1007/s10637-010-9426-2
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear transport capacity of a human-pancreatic ribonuclease variant is critical for its cytotoxicity

Abstract: We have previously described a human pancreatic-ribonuclease variant, named PE5, which carries a non-contiguous extended bipartite nuclear localization signal. This signal comprises residues from at least three regions of the protein. We postulated that the introduction of this signal in the ribonuclease provides it with cytotoxic activity because although the variant poorly evades the ribonuclease inhibitor in vitro, it is routed to the nucleus, which is devoid of the inhibitor. In this work, we have investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…RUNX1 is important for hematopoiesis and its ablation leads to leukemia, and RUNX3 is a critical regulator and its promoter hypermethylation is associated with several types of cancer. [3][4][5][6] These findings strongly suggest that RUNX1 and RUNX3 function as tumor suppressors. The RUNX2 gene, on the other hand, is a unique member of the RUNX family that was shown to have a dual function in several studies.…”
Section: Introductionmentioning
confidence: 81%
“…RUNX1 is important for hematopoiesis and its ablation leads to leukemia, and RUNX3 is a critical regulator and its promoter hypermethylation is associated with several types of cancer. [3][4][5][6] These findings strongly suggest that RUNX1 and RUNX3 function as tumor suppressors. The RUNX2 gene, on the other hand, is a unique member of the RUNX family that was shown to have a dual function in several studies.…”
Section: Introductionmentioning
confidence: 81%
“…The different mechanisms are likely related to their mechanism of action. Onconase is driven into the cytoplasm and its natural substrates are t-RNA and most probably the non-coding RNA (microRNA) [53] whereas PE5 is located in the nucleolus [10] and targets nuclear RNA [12]. Interestingly, nucleolus and biogenesis of rRNA are important factors distinguishing cancer from normal cells and may have an active role in tumorigenesis [54].…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear import assays showed that PE5 was efficiently transported to the nucleus where it was initially localized in the nucleolus. The variant carries a conformational bipartite nuclear localization signal [11] which targets the protein to the nucleus, specifically in the nucleolus [10], where RI is absent, therefore producing the degradation of nuclear RNA [12]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative strategy to engender RI-evasion is to bypass RI contact altogether. The human ptRNase variant PE5 carries a non-contiguous nuclear localization signal and has been shown to possess potent cytotoxicity that is dependent upon its nuclear uptake (Tubert et al , 2011). …”
Section: Attributes Of Cytotoxic Ptrnasesmentioning
confidence: 99%